Factors associated with mammography screening decision among rural women in Kiulu, Sabah - Godulus, Farhannidaline (Universiti Sains Malaysia, 2012)
Breast cancer is the common cancer and the leading cause of death among women in Malaysia. Mammography screening behavior has not been well studied among rural women in Sabah. Knowledge about breast cancer and screening were associated with mammography utilization. The objective of this study was to identify factors associated with mammography screening decision among rural women in Kiulu, Sabah. This study had a cross-sectional design with purposive sampling (n=200). A self-administered structured questionnaire was done. Data was analyzed using IBM Statistical Package Social Science (SPSS) software version 19.0. Of 200 participants, only 40 (20%) women had a mammogram done and 80% reported not had a mammogram. Chi-Square test revealed that age, ethnicity and marital status were associated with mammography screening decision with (p<0.05). Women 30 to 40 with mean age 41.86 years old were the highest respondents. 25 from 40 women 30- 40 years old more likely had a mammogram. Women who had reporting a mammogram were likely to be a Dusun woman, and were married. Meanwhile, the educational level and family history of breast cancer were found not associated with mammography screening decision (p>0.05). Using the Independent t-Test, perceived seriousness and barriers found was associated with mammography utilization. Women who had a mammogram score fewer on barriers (14.07). Specific barriers were identified among rural women in this study were embarrassment due to mammogram, causing pain, unpleasant and cost of mammogram. The findings also revealed that there was no association of knowledge about breast cancer screening and mammography utilization (p=0.884). This study provides valuable information for future study and research about belief and attitude toward breast cancer screening among rural women.